Impact of Corporate Social Responsibility on Job Satisfaction of Teaching Personnel in a Private Educational Institution in the Philippines - John Rex V Hermoso; Suzette A Laguartilla; Violeta R Salapare; Jesus P Briones; Joanna Paula E Verano (Research Synergy Foundation, 2025)
Corporate social responsibility (CSR) has evolved into a strategic framework for institutional development that integrates ethical practices, social welfare, and environmental stewardship across various sectors, including education. This study evaluated the impact of CSR dimensions – namely awareness, implementation, community impact, environmental accountability, and institutional commitment – on job satisfaction's facets including work environment, compensation and benefits, career growth and development, employee engagement, and tenure, focusing on 151 teaching personnel in a private educational institution (PEI) in the Philippines. Employing a descriptive-quantitative design, data were collected through a validated questionnaire distributed via Google Forms and in person, and analysed using frequency distributions, percentages, weighted means, and Pearson correlation coefficients (r). The findings revealed that the institution's CSR implementation is well-executed, implying that CSR practices are deeply embedded in the institution's culture. Furthermore, the study revealed that teaching personnel are delighted across all dimensions of job satisfaction, which highlights that the institution successfully fosters a work environment conducive to faculty loyalty, professional fulfilment, and emotional commitment. Consequently, the Pearson's correlation coefficient (r) revealed that CSR implementation is strongly and significantly related to job satisfaction. This finding suggests that authentic CSR practices not only enhance external reputation but also play a crucial role in faculty motivation, engagement, and retention. Theoretically, the study reinforces Stakeholder's Theory, affirming that internal stakeholders must be central in designing and implementing CSR initiatives to achieve sustainable institutional growth.